Materials for Architects and Builders - Lyons, Arthur (Arthur R.) (Amsterdam ; London : Butterworth-Heinemann, 2010)
A necessary purchase for level 1 and 2 undergraduates studying building/construction materials modules, this text provides an introduction to the broad range of materials used within the construction industry and contains information pertaining to their manufacture, key physical properties, specification and uses.
Previous ed.: 2007.
Includes bibliographical references and index.
Keywords: Building materials; House and Home